Plasma Growth Hormone and Prolactin Levels in Healthy Sedentary Young Men after Short-Term Endurance Training under Hot Environment - İbrahim Cicioglu; Fatih Kiyici (Montenegrin Sports Academy, 2013)
Pituitary hormones play an important role energy expenditure and body temperature regulation during exercise. The aim of the stu¬dy was to investigate the effect of two different endurance training in ambient temperature (30.76 ± 1.71oC and 57.92 ± 5.80% r.h.) on plasma growth hormone (GH) and prolactin (PRL) levels in non-trained healthy subjects. Twenty-four untrained healthy men participated in an 8-wk progressive two different endurance-training program. Subjects were divided into two groups: an in¬ter¬val running group (IR), and continuous running group (CR). Both groups were performed 3 days/wk. Growth hormone, PRL and VO2max levels were assessed at the beginning and the end of the training period. Body temperature (TB) was also measured at the be¬ginning and immediately after each training. The exercise type affected plasma PRL (8.52 vs. 6.50 ng/ml IR and CT groups, P < 0.02) but did not alter plasma GH levels (0.95 vs 0.63 ng/ml IR and CT groups, P>0.38). Plasma GH level at the end of training pro¬gram increased from 0.42 to 1.48 ng/ml and 0.58 to 0.67 ng/ml for IR and CR groups. Expectedly, both training types increased TB, at a greater rate for IR group than CR group. In conclusion, an 8-wk regular exercise result in an increase in plasma PRL level, with¬out altering plasma GH level, which accompanied by elevated body temperature, regardless of the individual's sporting rou¬ti¬ne. These suggest that untrained individuals could benefit from a regular exercise program as much as those doing the routine sport.